Malignant Mixed Mullerian Tumor Arising from Endometriosis in the Groin: A Case Report and Literature Review. (May 2023) - Yao, Ruisheng; Wu, Peter; Sung, C. James; Lamson, Jill A.; Zhang, Cunxian
This was a 57-year-old woman who presented with mild discomfort in the right groin. Physical examination revealed a mass in the right groin, and by ultrasound, the mass was hypoechoic and solid with some internal vascularity. The clinical differential diagnosis included lymphoma and others. The mass was excised for pathologic evaluation. Gross examination of the specimen revealed a 3 × 2.4 × 2 cm, solid and cystic mass. Microscopically, it was a biphasic tumor consisting of carcinomatous and sarcomatous components. The tumor was seen contiguous with endometriosis and atypical endometrioid hyperplasia. The histologic findings were consistent with malignant mixed Mullerian tumor (MMMT) arising from endometriosis in the right groin. The tumor involved the resection margin. Subsequent chest/abdominal/pelvic computed tomography did not reveal evidence of tumors, and diagnostic peritoneal/pelvic laparoscopy did not show diseases. Postoperatively, the patient received 6 cycles of chemotherapy consisting of carboplatin and paclitaxel, followed by radiation in the right groin. Malignant transformation from endometriosis occurs in less than 1% of endometriosis cases, and about 80% of the transformed tumors occur in the ovaries. The most commonly transformed malignant tumors are endometrioid and clear cell carcinomas, with rare adenosarcoma and endometrial stromal sarcoma reported. To our knowledge, we are reporting the first case of MMMT arising from endometriosis in the groin.